2014
DOI: 10.1016/j.vaccine.2014.07.098
|View full text |Cite
|
Sign up to set email alerts
|

Primary care providers human papillomavirus vaccine recommendations for the medically underserved: A pilot study in U.S. Federally Qualified Health Centers

Abstract: Introduction In the United States, Federally Qualified Health Centers (FQHCs) are safety-net clinics that provide cervical cancer screening and human papillomavirus (HPV) vaccination to medically underserved women, some of whom may be at risk for developing cervical cancer. National guidelines recommend against using screening test results or sexual history to determine vaccine eligibility. Documenting HPV vaccine recommendations and beliefs of primary care providers in FQHCs may aid in promoting evidence-base… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(19 citation statements)
references
References 21 publications
1
18
0
Order By: Relevance
“…5,6 We also found that about 66% of physicians reported they often or always recommended HPV vaccination to patients with an abnormal Pap test result, compared to 79–85% who sometimes to always did so in previous research. 5,6 Differences in analyses may have accounted for the lower proportion of physicians adhering to this practice recommendation in our study. In our study, we did not consider a sometimes response to reflect sufficiently consistent adherence to practice guidelines.…”
Section: Discussionsupporting
confidence: 52%
See 1 more Smart Citation
“…5,6 We also found that about 66% of physicians reported they often or always recommended HPV vaccination to patients with an abnormal Pap test result, compared to 79–85% who sometimes to always did so in previous research. 5,6 Differences in analyses may have accounted for the lower proportion of physicians adhering to this practice recommendation in our study. In our study, we did not consider a sometimes response to reflect sufficiently consistent adherence to practice guidelines.…”
Section: Discussionsupporting
confidence: 52%
“…1 ACIP does not recommend using prevaccination assessments to determine the appropriateness of HPV vaccination; 2,3 thus, physicians should not use Papanicolaou (Pap) or HPV test results to determine whether to offer HPV vaccination, nor should they use vaccine receipt to inform cervical cancer screening practices. Yet, available studies suggest many providers who deliver cervical cancer screening services for women report intended 4 or actual 5,6 practices inconsistent with ACIP recommendations, including failing to recommend HPV vaccine for females with a history of an abnormal Pap test or positive HPV test.…”
Section: Introductionmentioning
confidence: 99%
“…52,63 Provider communication was consistently associated with patients' sex such that providers' recommendation intentions and behavior were more supportive of HPV vaccination for girls versus boys. 10,12,24,25,29,33,37,44,55,57,58,60,64,65 For example, the 2014 NIS-Teen found that 64% of age-eligible girls had received a provider recommendation compared to just 42% of boys. 10 All but one study examining patients' race/ethnicity suggested disparities in provider communication with parents of African American and Hispanic adolescents less often discussing HPV vaccine with a provider or receiving HPV recommendations than parents of non-Hispanic White adolescents.…”
Section: Preferences In Communication Source By Provider Typementioning
confidence: 99%
“…19,33,38,44,74 Similarly, some providers based their HPV vaccine recommendations on risk-related factors such as the results of a Pap or HPV test, number of sexual partners, or relationship status. 52,58,75 Ironically, providers in one qualitative study acknowledged that their ability to accurately assess whether adolescents were sexually active was limited. 38 …”
Section: Preferences In Communication Source By Provider Typementioning
confidence: 99%
“…Three important factors that contribute to poor vaccine uptake are amenable to change. Many healthcare providers miss opportunities to recommend and administer the vaccine, [22][23][24] in part due to absent or low-quality recommendations [25]. Significant parental barriers exist, including parents' concerns about vaccine safety and cost, lack of knowledge, and failure to receive a provider recommendation [26][27][28].…”
Section: Need For Improved Hpv Vaccine Coverage For Cancer Preventionmentioning
confidence: 99%